THE ROLE OF INPUT, INTERACTION, AND NEGOTIATION IN SECOND LANGUAGE ACQUISITION - Dio Resta Permana (Linguists : Journal Of Linguistics and Language Teaching, 2018)
It has been still debatable whether someone acquire second language acquistion similar to first language or not especially in field of input. Input is one of the most important elements in the process of second language acqusition. Without input, learning second language cannot take place. In this paper, two hypotheses of input processing have been described based on Krashen’s input hypothesis and Long’s interaction hypothesis in order to see its influence in second language acquisition.